Alkaline developing resin composition, photocurable dry film thereof, cured product thereof, and printed wiring board formed using the same
By adding vinyl ester resin, photopolymerization initiator and antioxidant to the resin composition, and adjusting the proportion of inorganic fillers, the problem of the resin being prone to cracking during high temperature storage and hot and cold cycles is solved, and stability at high temperature and good performance of printed circuit boards are achieved.
Patent Information
- Application Number
- JP2024543263
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2023-12-27
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-12-27
AI Technical Summary
The acidic development resins in the prior art are prone to cracking during high temperature storage and hot and cold cycles, and are insufficient in printing and stability (such as tin plating resistance and boiling resistance), making it difficult to meet the long-term reliability needs in special environments such as automobiles.
A new alkaline development resin composition is formed by adjusting the filler ratio and adding antioxidants to form a new alkaline development resin composition using a composition containing ethylene unsaturated groups, a photopolymerization initiator, an antioxidant and an inorganic filler such as barium sulfate and zinc oxide.
It improves the resistance to hot and cold impact, high temperature resistance, acid resistance and tin coating of the resin, maintains good printing properties and stability, and is suitable for the production of printed circuit boards.
Smart Images

Figure 2025503072000010 
Figure 2025503072000011 
Figure 2025503072000012
Abstract
Description
[Technical field]
[0001] The present invention relates to an alkaline developable resin composition suitable for forming a solder resist film or the like on a printed wiring board, a photocurable dry film thereof, and a cured product thereof, and in particular to an alkaline developable resin composition capable of forming a solder resist film having good printability and excellent thermal shock resistance, a photocurable dry film thereof, and a cured product thereof, and a printed wiring board. [Background technology]
[0002] At present, for the formation of solder resist films (solder resists) for some consumer printed wiring boards and most industrial printed wiring boards, an alkaline development type solder resist agent is used, which is exposed to ultraviolet light, developed to form a pattern, and completely cured (mainly cured) by heat and / or light irradiation. Also, for semiconductor devices used in vehicles such as automobiles, trains, ships, and aircraft, and communication devices used in special environments, there is a tendency for solder resist agents for long-term, highly reliable electronic materials to be used as solder resist agents for printed wiring boards.
[0003] However, general alkaline development type solder resists usually have poor crack resistance during thermal cycles and poor high-temperature storage stability due to thermal expansion, etc. Although general solder resist uses can be satisfied by selecting barium sulfate as a filler, it has poor crack resistance during thermal cycles and poor high-temperature storage stability, which are required for applications such as in-vehicle mounting. It also has a negative effect on the printability (covering ability, sagging) and stability (tin plating resistance, boil whitening resistance) of the ink.
[0004] For example, the photocurable solder resist of Patent Document 1 uses silica, barium sulfate, and talc as fillers. The curable resin composition for solder resist film of Patent Document 2 contains a carboxyl group-containing resin, a thermosetting component, a flame retardant, and an ion trapping agent, and the ion trapping agent is a mixture of a hydrotalcite-based ion trapping agent and an ion trapping agent other than hydrotalcite-based ion trapping agent, and aluminum hydroxide is used as an inorganic filler. The curable resin composition of Patent Document 3 is used as a permanent mask for printed wiring boards, and contains a resin containing an ethylenically unsaturated group and a carboxyl group in the molecule, a photopolymerization initiator, a photopolymerizable monomer, titanium oxide surface-treated with alumina, barium sulfate and / or talc, and an organic solvent. Patent Document 4 describes that the filler of the ultraviolet light-curable liquid photosensitive solder resist flexible ink is barium sulfate, talc, or silica. [Prior art documents] [Patent documents]
[0005] Patent document 1: CN114716868A Patent document 2: CN108137791A Patent document 3: CN101798432A Patent document 4: CN106380929A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an alkaline developable resin composition capable of forming a solder resist film which has good printability (covering ability, sagging) and stability (tin plating resistance, boil whitening resistance) and is excellent in both cold and heat shock resistance and high-temperature storage stability, a photocurable dry film thereof, a cured product thereof, and a printed wiring board. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and have found that the filler and antioxidant have a significant effect on the above performance. The following alkaline development type resin composition can solve the above problems, and has completed the present invention. The alkaline development type resin composition contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) an antioxidant, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, and is characterized in that, when the total amount of the (E) inorganic filler is taken as 100% by weight, the content of the talc is 50% by weight or more, and the total content of the (E) inorganic filler is 60 to 180 parts by weight per 100 parts by weight (solid content equivalent) of the (A) vinyl ester resin.
[0008] That is, the alkaline developable resin composition of the present invention contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) an antioxidant, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, and is characterized in that, when the total amount of the (E) inorganic filler is taken as 100% by weight, the content of the talc is 50% by weight or more, and the total content of the (E) inorganic filler is 60 to 180 parts by weight per 100 parts by weight (converted into solid content) of the (A) vinyl ester resin.
[0009] It is also preferred to contain (F) other additives other than the (B) photopolymerization initiator and (C) antioxidant.
[0010] It is also preferable that the composition contains an epoxy resin (G).
[0011] It is also preferred that the solvent contains an organic solvent (H).
[0012] Moreover, the amount of the (C) antioxidant used is preferably 3 parts by weight or more based on 100 parts by weight (solid content) of the (A) vinyl ester resin.
[0013] Moreover, it is preferable that the (E) inorganic filler further contains barium sulfate.
[0014] The photocurable dry film of the present invention is characterized in that it is obtained by applying the alkaline developing resin composition to a carrier film and drying it.
[0015] The cured product of the present invention is characterized in that it is obtained by applying the alkaline developable resin composition to copper and drying the coating film, or by applying the alkaline developable resin composition to a carrier film, drying the resulting photocurable dry film, and laminating the resulting coating film on copper, followed by photocuring the resulting coating film.
[0016] The printed wiring board of the present invention is characterized in that it is obtained by applying the alkaline developable resin composition to a substrate having a copper circuit and drying the composition to obtain a coating film, or by applying the alkaline developable resin composition to a carrier film, drying the composition, and laminating the resulting photocurable dry film onto a substrate having a copper circuit to obtain a coating film, followed by photocuring and then thermal curing the coating film.
[0017] The alkaline developable resin composition of the present invention contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) an antioxidant, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, and is most characterized in that, when the total amount of the (E) inorganic filler is taken as 100% by weight, the content of the talc is 50% by weight or more, and the total content of the (E) inorganic filler is 60 to 180 parts by weight per 100 parts by weight (converted into solid content) of the (A) vinyl ester resin.
[0018] Based on the characteristic configuration of the present invention, by using an antioxidant and talc in combination and adjusting the amounts of each used, it is possible to obtain a solder resist film that is excellent in all of thermal shock resistance, high-temperature storage stability, and acid resistance while maintaining the good printability (covering ability, sagging) and stability (tin plating resistance, boil whitening resistance) of the alkaline developing type resin composition.
[0019] In contrast, in conventional technology, the use of talc and barium sulfate as a filler in combination improves acid resistance, tin plating resistance, and boil whitening resistance, but deteriorates printability, thermal shock resistance, and high-temperature storage stability (for example, Patent Document 1, etc.).
[0020] As a result of intensive research, the inventors have found that talc as a filler has good flexibility, excellent crack resistance in a temperature cycle test (hereinafter sometimes abbreviated as "TCT test"), and excellent high-temperature storage stability in a temperature shock test (hereinafter sometimes abbreviated as "TS test"), but the acid resistance deteriorates as the amount used increases. Barium sulfate, a conventional filler, can improve acid resistance, but has poor cold and heat shock resistance and high-temperature storage stability. Even if the amount of both is increased at the same time, the high-temperature storage stability, acid resistance, and stability (tin plating resistance, boil whitening resistance) can be improved, but the cold and heat shock resistance and printability (covering property, sagging) are still poor. On the other hand, by adding an antioxidant, the acid resistance and stability (tin plating resistance, boil whitening resistance) can be improved without affecting the printability. In other words, the combined use of an antioxidant and talc has the surprising effect of providing a solder resist film that is excellent in all respects, including thermal shock resistance, high-temperature storage stability, acid resistance, tin plating resistance, and boil whitening resistance, while maintaining good printability (covering ability, sagging), thereby achieving the object of the present invention. Effect of the Invention
[0021] As described above, according to the present invention, it is possible to provide an alkaline developable resin composition which has good printability (covering ability, sagging) and stability (tin plating resistance, boil whitening resistance) and is capable of forming a solder resist film which is excellent in both cold / hot shock resistance and high-temperature storage stability, a photocurable dry film thereof, a cured product thereof, and a printed wiring board. [Brief description of the drawings]
[0022] [Figure 1] 1 is a photograph showing that cracks were generated in a solder resist film for evaluating thermal shock resistance in an example. [Diagram 2] 1 is a photograph showing that no cracks were generated in a solder resist film for evaluating thermal shock resistance in an example. [Diagram 3] 1 is a photograph showing that no peeling occurred in a cross-cut test for evaluating high-temperature storage stability in an example. [Figure 4] 1 is a photograph showing the coating thickness of an alkaline developing resin composition on a copper corner for evaluating covering ability in the examples. [Diagram 5] FIG. 2 is an image showing how the length of a drip of an alkaline developing resin composition from a reference line is measured in an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Each of the components of the alkaline developing resin composition of the present invention will be described below.
[0024] The alkaline developing resin composition of the present invention contains an antioxidant (C) and an inorganic filler (E), the inorganic filler (E) contains talc, and when the total amount of the inorganic filler (E) is taken as 100% by weight, the content of the talc is 50% by weight or more, and the total content of the inorganic filler is 60 to 180 parts by weight per 100 parts by weight (solid content equivalent) of the vinyl ester resin (A). Therefore, the antioxidant (C) and the inorganic filler (E) will be described first.
[0025] (C) Antioxidants The photosensitive resin composition of the present invention may contain an antioxidant such as a radical scavenger that eliminates generated radicals, or a peroxide decomposer that decomposes generated peroxides into harmless substances and prevents the generation of new radicals. The antioxidant used in the present invention can prevent oxidative deterioration of resins and the like, and further suppress yellowing. Furthermore, when the inorganic filler contains talc, the addition of an antioxidant can significantly improve the acid resistance of the solder resist film and the stability of the ink (tin plating resistance, boil whitening resistance) in addition to the above effects. The antioxidants may be used alone or in combination of two or more.
[0026] As the antioxidant (C) used in the alkaline developing resin composition of the present invention, an antioxidant that functions as a radical scavenger is preferred, from the viewpoint of being more advantageous in achieving the object of the present invention.
[0027] Examples of antioxidants that function as radical scavengers include hydroquinone, 4-tert-butylcatechol, 2-tert-butylhydroquinone, hydroquinone monomethyl ether, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), 2,6-di-tert-butyl-p-cresol, 2,2-methylenebis(4-methyl-6-tert-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert phenolic compounds such as 1,3,5-tris(3',5'-di-tert-butyl-4-hydroxybenzyl)-triazine-2,4,6-(1H,3H,5H)trione, p-methoxyphenol, quinone compounds such as benzoquinone, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, and amine compounds such as phenothiazine. Examples of commercially available products include ADEKASTAB AO-30, ADEKASTAB AO-330, ADEKASTAB AO-20, ADEKASTAB LA-77, ADEKASTAB LA-57, ADEKASTAB LA-67, ADEKASTAB LA-68, ADEKASTAB LA-87 (all of which are product names manufactured by ADEKA CORPORATION), IRGANOX 1010, IRGANOX 1035, IRGANOX 1076, IRGANOX 1135, TINUVIN 111FDL, TINUVIN 123, TINUVIN 144, TINUVIN 152, TINUVIN 292, TINUVIN 5100 (all of which are product names manufactured by BASF JAPAN LTD.), and CHINOX TP-10H (product name manufactured by DOUBLE BOND CHEMICAL IND.CO.,LTD.).
[0028] Examples of antioxidants that function as peroxide decomposers include phosphorus compounds such as triphenyl phosphite, and sulfur compounds such as pentaerythritol tetrakis-(3-lauryl thiopropionate), dilauryl thiodipropionate, and dioctadecyl 3,3'-thiodipropionate. Commercially available products include ADEKASTAB TPP (manufactured by ADEKA CORPORATION, product name), MARK AO-412S (manufactured by ADEKA CORPORATION, product name), and Sumilizer TPS (manufactured by Sumitomo Chemical Co., Ltd., product name).
[0029] The blending ratio of the (C) antioxidant is suitably 0.1 to 20 parts by weight, preferably 1 to 15 parts by weight, more preferably 3 to 12 parts by weight, and further preferably 3 to 10 parts by weight, per 100 parts by weight (solid content equivalent) of the (A) vinyl ester resin. When the amount of the (C) antioxidant used is within the above range, it is possible to ensure a significant improvement in the acid resistance of the solder resist film and the stability of the ink (tin plating resistance, boil whitening resistance) without adversely affecting the printability.
[0030] (E) Inorganic filler As described above, in the alkaline developing resin composition of the present invention, the talc used as the inorganic filler (E) is used to improve the thermal shock resistance and high-temperature storage stability.
[0031] The talc may be any one of magnesium carbonate, serpentine, silica / silica-alumina, and magnesium deposits, and may be any one of so-called silicate minerals, and may be in the form of a lump or fine powder. Surface treatment may or may not be performed. The average particle size of the talc is suitably 1.0 to 20.0 μm, more preferably 2.0 to 10 μm, and further preferably 3.0 to 8.0 μm. Examples of commercially available products include HD25 manufactured by Talc Mining Co., Ltd., Pingdu City, Shandong Province, and LMP-100 manufactured by Fuji Talc Industry Co., Ltd. If the (E) inorganic filler is composed of only talc, the printability is particularly excellent.
[0032] Talc can improve the printability of an alkaline developing resin composition and the thermal shock resistance and high-temperature storage stability of a solder resist film, but the acid resistance deteriorates as the amount used increases. Therefore, in order to ensure the achievement of each effect of the present invention, when the total amount of the (E) inorganic filler is taken as 100% by weight, the content of talc is suitably 50% by weight or more, more preferably 55% by weight or more, and even more preferably 60% by weight or more.
[0033] Fillers other than talc, such as barium sulfate, may be blended within the scope of the present invention. Although the use of barium sulfate can improve acid resistance, the use of a large amount of barium sulfate adversely affects the printability (covering ability, sagging) and stability (tin plating resistance, boiling whitening resistance) of the alkaline developing resin composition, as well as the thermal shock resistance and high temperature storage stability of the solder resist film.
[0034] Commercially available barium sulfate products include B-30, B-31, B-32, B-33, B-34, B-35, and B-35T manufactured by Sakai Chemical Industry Co., Ltd.
[0035] Examples of the shape of the inorganic filler include spherical, needle-like, sheet-like, scaly, hollow, irregular, hexagonal, cubic, and flake-like shapes.
[0036] From the viewpoint of achieving both the printability of the alkaline developable resin composition and the thermal shock resistance and high-temperature storage stability of the solder resist film, the total content of the inorganic filler is appropriately 60 to 180 parts by weight, more preferably 80 to 160 parts by weight, and even more preferably 90 to 150 parts by weight, relative to 100 parts by weight (converted into solid content) of the (A) vinyl ester resin.
[0037] (A) Vinyl ester resin As the vinyl ester resin (A) in the photocurable thermosetting resin composition of the present invention, a known resin having an ethylenically unsaturated double bond in the molecule can be used from the viewpoint of photocurability and development resistance. In addition, in order to impart alkaline developability, a carboxyl group-containing resin having an ethylenically unsaturated double bond in the molecule is particularly preferred. In addition, the unsaturated double bond is more preferably derived from acrylic acid or methacrylic acid or a derivative thereof. As the vinyl ester resin (A), a resin using an epoxy resin as a starting material, a polyurethane resin having a urethane skeleton, a copolymer resin having a copolymer structure of an unsaturated carboxylic acid, or a resin using a phenol compound as a starting material is preferred. Specific examples of the vinyl ester resin (A) are shown below. (1) A vinyl ester resin obtained by copolymerizing an unsaturated carboxylic acid such as (meth)acrylic acid with one or more other compounds having an unsaturated double bond. (2) Photosensitive vinyl ester resins obtained by adding an ethylenically unsaturated group as a side group to a copolymer of an unsaturated carboxylic acid such as (meth)acrylic acid and one or more other compounds having an unsaturated double bond, using a compound having an epoxy group and an unsaturated double bond, such as glycidyl (meth)acrylate or 3,4-epoxycyclohexylmethyl (meth)acrylate, or (meth)acrylic acid chloride, etc.; (3) A photosensitive vinyl ester resin obtained by reacting a copolymer of a compound having an epoxy group and an unsaturated double bond, such as glycidyl (meth)acrylate or 3,4-epoxycyclohexylmethyl (meth)acrylate, with an unsaturated carboxylic acid, such as (meth)acrylic acid, and then reacting the resulting secondary hydroxyl group with a polybasic acid anhydride. (4) A photosensitive vinyl ester resin obtained by reacting a copolymer of an acid anhydride having an unsaturated double bond, such as maleic anhydride, and another compound having an unsaturated double bond with a compound having a hydroxyl group and an unsaturated double bond, such as 2-hydroxyethyl (meth)acrylate. (5) A vinyl ester resin obtained by reacting a polyfunctional epoxy compound with an unsaturated monocarboxylic acid and reacting the resulting hydroxyl group with a saturated or unsaturated polybasic acid anhydride. (6) A vinyl ester resin containing hydroxyl groups and carboxyl groups, which is obtained by reacting a hydroxyl group-containing polymer such as a polyvinyl alcohol derivative with a saturated or unsaturated polybasic acid anhydride, and then reacting the resulting carboxylic acid with a compound having an epoxy group and an unsaturated double bond in one molecule. (7) A vinyl ester resin obtained by reacting a reaction product of a polyfunctional epoxy compound, an unsaturated monocarboxylic acid, and a compound having in one molecule at least one alcoholic hydroxyl group and one reactive group other than the alcoholic hydroxyl group that reacts with an epoxy group, with a saturated or unsaturated polybasic acid anhydride. (8) A vinyl ester resin obtained by reacting a polyfunctional oxetane compound having at least two oxetane rings in one molecule with an unsaturated monocarboxylic acid, and reacting a primary hydroxyl group in the resulting modified oxetane resin with a saturated or unsaturated polybasic acid anhydride; and (9) A vinyl ester resin obtained by reacting a polyfunctional epoxy resin with an unsaturated monocarboxylic acid, followed by reaction with a polybasic acid anhydride to obtain a carboxyl group-containing resin, and then reacting the resulting resin with a compound having one oxirane ring and one or more ethylenically unsaturated groups in the molecule; (10) A vinyl ester resin obtained by reacting an unsaturated monocarboxylic acid with a bifunctional epoxy compound and then reacting the resulting hydroxyl group with a saturated or unsaturated polybasic acid anhydride.
[0038] Among these examples, the vinyl ester resins (2), (5), (7) and (9) are particularly preferred.
[0039] In this specification, (meth)acrylate is a term that collectively refers to acrylate, methacrylate, and mixtures thereof, and the same applies to other similar expressions hereinafter.
[0040] The vinyl ester resin (A) described above has a plurality of free carboxyl groups in the side chains of the main chain polymer, and therefore can be developed using a dilute aqueous alkali solution. In this specification, the term "polymer" is a general term for homopolymers, copolymers and mixtures thereof, and the same applies to other similar expressions.
[0041] The acid value of the vinyl ester resin (A) is preferably in the range of 40 to 200 mgKOH / g, more preferably in the range of 45 to 120 mgKOH / g. If the acid value of the carboxyl group-containing resin is less than 40 mgKOH / g, alkaline development becomes difficult, while if it exceeds 200 mgKOH / g, the exposed area is dissolved in the developer, resulting in lines that are thinner than necessary, or in some cases, the exposed area and the unexposed area are dissolved and peeled off in the developer without distinction, making it difficult to draw a normal resist pattern, which is undesirable.
[0042] The weight-average molecular weight of the vinyl ester resin (A) varies depending on the resin skeleton, but is generally in the range of 2,000 to 150,000, and more preferably 5,000 to 100,000. If the weight-average molecular weight is less than 2,000, the tack-free performance after application to a substrate and drying may be poor, and the moisture resistance of the coating film after exposure may be poor, film loss may occur during development, and resolution may be significantly poor. On the other hand, if the weight-average molecular weight exceeds 150,000, the developability may be significantly poor and storage stability may be poor.
[0043] The amount of the vinyl ester resin (A) is desirably in the range of 20 to 60 mass % of the total composition, and preferably 25 to 50 mass %, calculated as solid content. If the amount of the vinyl ester resin (A) is less than the above range, the strength of the coating film is reduced, which is not preferable. On the other hand, if the amount is more than the above range, the viscosity of the composition increases or the coatability is reduced, which is not preferable.
[0044] (B) Photopolymerization initiator The photopolymerization initiator used in the alkaline developing type resin composition of the present invention is not particularly limited as long as it is a photopolymerization initiator generally used in alkaline developing type resin compositions.
[0045] As the photopolymerization initiator, known ones can be used, including benzoin and its alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, and 4-(1-t-butyldioxy-1-methylethyl)acetophenone; anthraquinones such as 2-methylanthraquinone, 2-amylanthraquinone, 2-t-butylanthraquinone, and 1-chloroanthraquinone. thioxanthone, such as isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, and 2,4-chlorothioxanthone; ketals, such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzophenone, 4-(1-t-butyldioxy-1-methylethyl)benzophenone, and 3,3',4,4'-tetrakis(t-butyldioxycarbonyl)benzophenone; and oxoanthracene.
[0046] In addition, as the photopolymerization initiator, an oxime ester-based photopolymerization initiator having an oxime ester group, an alkylphenone-based photopolymerization initiator, an α-aminoacetophenone-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, a titanocene-based photopolymerization initiator, a phosphate-based photopolymerization initiator, or the like can also be used.
[0047] Commercially available oxime ester photopolymerization initiators include Irgacure OXE01 and Irgacure OXE02 manufactured by BASF Japan, and N-1919 and NCI-831 manufactured by ADEKA CORPORATION. A photopolymerization initiator having two oxime ester groups in the molecule can be suitably used, and specifically, an oxime ester compound having a carbazole structure can be mentioned.
[0048] Commercially available alkylphenone photopolymerization initiators include α-hydroxyalkylphenones such as Omnirad 184, Omnirad 1173, Omnirad 2959, and Omnirad 127 manufactured by IGM Resins BV.
[0049] Specific examples of the α-aminoacetophenone-based photopolymerization initiator include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, N,N-dimethylaminoacetophenone, etc. Commercially available products include Omnirad 907, Omnirad 369, Omnirad 379, etc. manufactured by IGM Resins BV.
[0050] Specific examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, trifunctional or higher acylphosphine photopolymerization initiators, etc. The trifunctional or higher acylphosphine photopolymerization initiator may be a photopolymerization initiator having three or more acylphosphine oxide skeletons in one molecule, and can be represented by the following formula (I). TIFF2025503072000001.tif28169In formula, A's are each independently a single bond, O, S or NR 3 represents G is a multifunctional compound (core) G-(AH) m+n where AH represents an alcohol group, an amino group, or a thiol group, m and n are both integers, and m+n is an integer between 3 and 10; m is an integer between 3 and 8; R1 and R2 are each independently a C1-C1 alkyl group that is uninterrupted or interrupted by one or more oxygen and / or sulfur atoms and / or one or more substituted or unsubstituted imino groups. 18 Alkyl groups, C6-C 12 Aryl groups and C5-C 12 or R1 and R2 are each independently a 5- to 6-membered heterocyclic group containing oxygen and / or nitrogen and / or sulfur atoms, which may be substituted with an aryl group, an alkyl group, an aryloxy group, an alkoxy group, a heteroatom and / or a heterocyclic group; R2 may be R1-(C=O)-; Y is O or S; R3 is hydrogen or a C1 to C4 alkyl group.
[0051] Here, the photopolymerization initiator represented by formula (I) does not contain a photocurable ethylenically unsaturated group.
[0052] Preferably, in formula (I), m+n is an integer between 3 and 8, more preferably an integer between 3 and 6. For example, in formula I, m is an integer between 3 and 6, more preferably an integer between 3 and 5.
[0053] In formula (I), when A is oxygen, G-(AH) m+n is a polyhydroxy compound selected from the group consisting of monomeric polyols, oligomeric polyols, and polymeric polyols, and mixtures thereof. When A is sulfur, G-(AH) m+n is a polythiol compound. In formula (I), when A is nitrogen, G-(AH) m+n is a linear or branched polyamine. When A is a mixture of oxygen and / or nitrogen and / or sulfur, G-(AH) m+n is a compound containing different functional groups, for example a compound containing an amino group and a hydroxy group. Residue G- suitable for carrying out the present invention does not contain a photocurable ethylenically unsaturated group. When A is a single bond, G- is the G-(AH) exemplified above. m+nIt is a residue obtained by removing a hydroxy group and / or an amino group and / or a mercapto group from the above.
[0054] Preferably, G-(AH) m+n The number average molecular weight is 1,500 or less, more preferably 800 or less, and even more preferably 500 or less.
[0055] When n is not 0, the compound of formula (I) has alcoholic free groups and / or amino groups and / or mercapto groups.
[0056] Representative trifunctional or higher acylphosphine photopolymerization initiators included in formula (I) are shown in Table 1. Among them, PI-3, PI-4, PI-10, PI-11, PI-12, PI-14, and PI-17 are particularly preferred. By including such trifunctional or higher acylphosphine photopolymerization initiators, outgassing is suppressed, and a cured product with superior insulation reliability can be obtained.
[0057] [Table 1] JPEG2025503072000003.jpg227166JPEG2025503072000004.jpg238167JPEG2025503072000005.jpg185167 JPEG2025503072000006.jpg136167JPEG2025503072000007.jpg220167JPEG2025503072000008.jpg106165
[0058] Such tri- or higher functional acylphosphine photopolymerization initiators can be produced by the method described in Japanese Patent No. 6,599,446, for example.
[0059] As commercially available acylphosphine oxide photopolymerization initiators, Omnirad TPO manufactured by IGM Resins, Omnirad 819 and Omnipol TP manufactured by IGM Resins BV, and the like can be used.
[0060] Specific examples of the titanocene photopolymerization initiator include bis(cyclopentadienyl)(diphenyl)titanium(IV), bis(cyclopentadienyl)titanium(IV) dichloride, bis(cyclopentadienyl)-bis(2,3,4,5,6-pentafluorophenyl)titanium(IV), bis(cyclopentadienyl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium(IV), etc. Commercially available products include Omnirad 784 manufactured by IGM Resins BV.
[0061] The blending ratio of these photopolymerization initiators (B) is suitably 0.01 to 30 parts by weight, preferably 5 to 25 parts by weight, and more preferably 10 to 20 parts by weight, relative to 100 parts by weight (solid content equivalent) of the vinyl ester resin (A). If the amount of the photopolymerization initiator used is less than the above range, the photocurability of the composition deteriorates, whereas if it is too much, the properties as a solder resist agent deteriorate, which is not preferable.
[0062] (D) Compounds having two or more ethylenically unsaturated groups in one molecule
[0063] The compound (D) having two or more ethylenically unsaturated groups per molecule used in the alkaline developing resin composition of the present invention is a compound that can be photocured by irradiation with active energy rays to make the vinyl ester resin (A) insoluble in an alkaline aqueous solution or to help make the vinyl ester resin insoluble in an alkaline aqueous solution. Specific examples of such compounds include: Hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxypropyl acrylate, Monoacrylates or diacrylates of glycols such as ethylene glycol, methoxytetraethylene glycol, polyethylene glycol, and propylene glycol; Acrylamides such as N,N-dimethylacrylamide, N-methylolacrylamide, and N,N-dimethylaminopropylacrylamide; Aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate and N,N-dimethylaminopropyl acrylate; Polyols such as hexanediol, trimethylolpropane, pentaerythritol, dipentaerythritol, tris(2-hydroxyethyl) isocyanurate, etc., or polyhydric acrylates such as ethylene oxide adducts or propylene oxide adducts thereof, acrylates such as phenoxy acrylate, bisphenol A diacrylate, and ethylene oxide or propylene oxide adducts of these phenols; acrylates of glycidyl ethers such as glycerin diglycidyl ether, glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanurate; and melamine acrylate, and at least one of the methacrylates corresponding to the above acrylates.
[0064] Further examples include epoxy acrylate resins obtained by reacting acrylic acid with a multifunctional epoxy resin such as a cresol novolac epoxy resin, and epoxy urethane acrylate compounds obtained by reacting a hydroxyl group of this epoxy acrylate resin with a half urethane compound of a hydroxyacrylate such as pentaerythritol triacrylate and a diisocyanate such as isophorone diisocyanate.
[0065] The amount of compound (D) having two or more ethylenically unsaturated groups in one molecule is preferably 5 to 100 parts by weight, more preferably 10 to 70 parts by weight, relative to 100 parts by weight of the vinyl ester resin (A) (based on solid content). If the amount is less than 5 parts by weight relative to 100 parts by weight of the vinyl ester resin (A), the photocurability of the resulting alkaline development type resin composition decreases, making it difficult to form a pattern by alkaline development after irradiation with active energy rays, which is not preferred. On the other hand, if the amount exceeds 100 parts by weight, the solubility in an alkaline aqueous solution decreases, making the cured coating film brittle, which is not preferred.
[0066] (F) Other additives As described above, the other additives in the present invention refer to additives other than the (B) photopolymerization initiator and the (C) antioxidant.
[0067] Examples of such additives include known and commonly used colorants such as phthalocyanine blue, phthalocyanine green, iodine green, disazo yellow, crystal violet, titanium oxide, carbon black, acid black, etc., known and commonly used thermal polymerization inhibitors, known and commonly used thickeners such as finely powdered silica, organic bentonite, montmorillonite, etc., at least one of silicone-based, fluorine-based, polymer-based, etc. defoaming agents and leveling agents, imidazole-based, thiazole-based, triazole-based, etc. adhesion imparting agents, silane coupling agents, hindered amine-based light stabilizers, etc.
[0068] The blending ratio of such (F) other additives is suitably 0.01% by weight or more and 20% by weight or less of the total amount of the alkaline developing resin composition. If it is less than 0.01% by weight, the effect is not sufficiently obtained, while if it exceeds 20% by weight, the printability and hardness of the alkaline developing resin composition are deteriorated, which is not preferable.
[0069] (G) Epoxy resin In order to impart heat resistance, it is preferable to blend an epoxy resin having at least two epoxy groups in the molecule, that is, a polyfunctional epoxy resin (G), in the alkaline developing resin composition used in the present invention.
[0070] Commercially available products include bisphenol A type epoxy resins such as jER828, jER834, jER1001, and jER1004 manufactured by Mitsubishi Chemical Corporation, EPICLON 840, 850, 850S, 1050, and 2055 manufactured by DIC Corporation, EPOTOTE YD-011, YD-013, YD-127, and YD-128 manufactured by NIPPON STEEL Chemical & Material Co., Ltd., DER317, DER331, DER661, and DER664 manufactured by Dow Chemical Company, and Sumi-Epoxy ESA-011, ESA-014, ELA-115, and ELA-128 manufactured by Sumitomo Chemical Co., Ltd. (all trade names); jERYL903 manufactured by Mitsubishi Chemical Corporation, EPICLON 152, EPICLON 165, and NIPPON STEEL Chemical & Material Co., Ltd. Brominated epoxy resins such as EPOTOTE YDB-400 and YDB-500 manufactured by Dow Chemical Company, DER542 manufactured by Dow Chemical Company, and Sumi-Epoxy ESB-400 and ESB-700 manufactured by Sumitomo Chemical Co., Ltd. (all under the trade name); jER152 and jER154 manufactured by Mitsubishi Chemical Corporation, DEN431 and DEN438 manufactured by Dow Chemical Company, EPICLON N-730, EPICLON N-770, and EPICLON N-865 manufactured by DIC Corporation, EPOTOTE YDCN-701 and YDCN-704 manufactured by NIPPON STEEL Chemical & Material Co., Ltd., EPPN-201, EOCN-1025, EOCN-1020, EOCN-104S, RE-306, and NC-3000 manufactured by Nippon Kayaku Co., Ltd., and Sumi-Epoxy manufactured by Sumitomo Chemical Co., Ltd. ESCN-195X, ESCN-220, NIPPON STEEL Chemical & Material Co., Ltd.Novolac type epoxy resins such as YDCN-700-2, YDCN-700-3, YDCN-700-5, YDCN-700-7, YDCN-700-10, YDCN-704, and YDCN-704A manufactured by Nippon Paint Chemical Co., Ltd., and EPICLON N-680, N-690, and N-695 (all trade names) manufactured by DIC Corporation; EPICLON 830 manufactured by DIC Corporation, jER807 manufactured by Mitsubishi Chemical Corporation, bisphenol F type epoxy resins such as EPOTOTE YDF-170, YDF-175, and YDF-2004 (all trade names) manufactured by NIPPON STEEL Chemical & Material Co., Ltd. Hydrogenated bisphenol A type epoxy resins such as ST-2004, ST-2007, ST-3000 (trade names), and YX8034 manufactured by Mitsubishi Chemical Corporation; jER604 manufactured by Mitsubishi Chemical Corporation, and NIPPON STEEL Chemical & Material Co., Ltd.glycidylamine type epoxy resins such as EPOTOTE YH-434 manufactured by Sumitomo Chemical Co., Ltd. and Sumi-Epoxy ELM-120 manufactured by Sumitomo Chemical Co., Ltd. (all trade names); hydantoin type epoxy resins; alicyclic epoxy resins such as CELLOXIDE 2021P manufactured by Daicel Corporation (trade name); trihydroxyphenylmethane type epoxy resins such as YL-933 manufactured by Mitsubishi Chemical Corporation and EPPN-501 and EPPN-502 manufactured by Nippon Kayaku Co., Ltd. (all trade names); bixylenol type or biphenol type epoxy resins or mixtures thereof such as YL-6056, YX-4000, and YL-6121 manufactured by Mitsubishi Chemical Corporation (all trade names); EBPS-200, ADEKA Bisphenol S type epoxy resins such as EPX-30 manufactured by CORPORATION and EXA-1514 (trade name) manufactured by DIC Corporation; bisphenol A novolac type epoxy resins such as jER157S (trade name) manufactured by Mitsubishi Chemical Corporation; tetraphenylolethane type epoxy resins such as jERYL-931 (trade name) manufactured by Mitsubishi Chemical Corporation; heterocyclic epoxy resins such as TEPIC (trade name) manufactured by Nissan Chemical Industries, Ltd.; diglycidyl phthalate resins such as BRENMAR DGT manufactured by NOF Corporation; tetraglycidyl xylenoylethane resins such as ZX-1063 manufactured by NIPPON STEEL Chemical & Material Co., Ltd.; Examples of epoxy resins that contain a naphthalene skeleton include ESN-190 and ESN-360 manufactured by Nippon Steel Chemical & Material Co., Ltd., HP-4032, EXA-4750, and EXA-4700 manufactured by DIC Corporation, glycidyl methacrylate copolymer epoxy resins such as CP-50S and CP-50M manufactured by NOF Corporation, and further include cyclohexylmaleimide and glycidyl methacrylate copolymer epoxy resins, and CTBN-modified epoxy resins (e.g., YR-102 and YR-450 manufactured by Nippon Steel Chemical & Material Co., Ltd.), but are not limited thereto. These epoxy resins may be used alone or in combination of two or more.
[0071] The content of the (G) epoxy resin is preferably 10 to 100 parts by weight, more preferably 20 to 90 parts by weight, and even more preferably 30 to 80 parts by weight, per 100 parts by weight (solid content) of the (A) vinyl ester resin.
[0072] (H) Organic Solvent Regarding the organic solvent (H) used in the alkaline developing type resin composition of the present invention, an organic solvent can be used for the purpose of synthesizing the (A) vinyl ester resin, preparing the composition, or adjusting the viscosity when applying the composition to a substrate or carrier film.
[0073] Examples of such organic solvents include ketones, aromatic hydrocarbons, glycol ethers, glycol ether acetates, esters, alcohols, aliphatic hydrocarbons, and petroleum-based solvents. More specifically, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, dipropylene glycol methyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, and propylene glycol butyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol, and propylene glycol; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. The organic solvents described above can be used alone or as a mixture of two or more kinds.
[0074] When the alkaline development type resin composition of the present invention is used in forming a solder resist film for a printed wiring board, the composition is adjusted to a viscosity suitable for the application method as necessary, and then applied to a printed wiring board on which a circuit has been formed in advance by a method such as screen printing, curtain coating, spray coating, or roll coating, and dried at a temperature of, for example, about 60 to 100°C as necessary to form a tack-free coating film. Next, the composition is selectively exposed to active light through a photomask on which a predetermined exposure pattern has been formed, and the unexposed area is developed with an alkaline aqueous solution to form a resist pattern. Furthermore, by heating to a temperature of, for example, about 140 to 180°C for thermal curing, the curing reaction of the epoxy resin (G) and the polymerization of the vinyl ester resin (A) can be promoted, and various properties such as heat resistance, solvent resistance, acid resistance, moisture absorption resistance, PCT resistance, adhesion, and electrical properties of the resulting resist film can be improved. The photocuring reaction may be further promoted by adding a UV irradiation step before or after thermal curing by heating.
[0075] The alkaline aqueous solution used in the development may be an alkaline aqueous solution of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, amines, etc. In addition, the irradiation light source used in the photocuring may be a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a semiconductor laser, a solid state laser, a xenon lamp, a metal halide lamp, etc. The alkaline developing resin composition of the present invention can be used in the form of a photocurable dry film obtained by applying the alkaline developing resin composition to a carrier film in advance and drying it, other than the method of applying the alkaline developing resin composition in liquid form directly to a substrate having a copper circuit. The case where the alkaline developing resin composition of the present invention is used as a photocurable dry film is shown below. The photocurable dry film has a structure in which a carrier film, a resin layer, and a peelable cover film used as required are laminated in this order. The resin layer is a layer obtained by applying the alkaline development type resin composition of the present invention to a carrier film and drying it. After forming the resin layer on the carrier film, a cover film is laminated on the resin layer to obtain a photocurable dry film. The carrier film is a thermoplastic film such as a polyester film having a thickness of 2 to 150 μm. The resin layer is formed by uniformly applying an alkaline developing resin composition to a carrier film with a thickness of 10 to 150 μm using a blade coater, lip coater, comma coater, film coater, or the like, and drying the composition. The cover film may be a polyethylene film, a polypropylene film, or the like, but it is preferable that the adhesive strength with the resin layer is smaller than that of the carrier film. The cured product of the present invention is obtained by applying an alkaline developable resin composition to copper and drying the resulting coating film, or by applying the alkaline developable resin composition to a carrier film, drying the resulting photocurable dry film, and laminating the resulting coating film on copper, followed by photocuring the resulting coating film. To prepare a cured product on a substrate having a copper circuit using a photocurable dry film, the cover film is peeled off, the resin layer and the substrate having a copper circuit are superimposed, and laminated using a laminator or the like to form a resin layer on the substrate having a copper circuit. The formed resin layer can be exposed to light, developed, and cured by heating in the same manner as above to form a cured product. The carrier film can be peeled off either before or after exposure. The alkaline developing resin composition is suitably used for forming a cured film on a printed wiring board, preferably a permanent insulating film, and particularly preferably a solder resist. Working Example
[0076] The present invention will be described in more detail with reference to examples and comparative examples, but the scope of the present invention and its embodiments are not limited thereto. "Parts" and "%" in the examples and comparative examples are by weight unless otherwise specified. The property values of the composition of this example are tested by the method described below.
[0077] Synthesis Example In a four-neck flask equipped with a stirrer and a reflux condenser, 214 parts of cresol novolac epoxy resin EPICLON N-695 (DIC, epoxy equivalent = 214) were added, and 103 parts of diethylene glycol monoethyl ether acetate and 103 parts of a petroleum-based hydrocarbon solvent (Japan Energy Corporation, product name: Cactus Fines SF-01) were added and dissolved by heating. Next, 0.1 parts of hydroquinone as a polymerization inhibitor and 2.0 parts of triphenylphosphine as a reaction catalyst were added. This mixture was heated to 95-105°C, 72 parts of acrylic acid were slowly dropped, and the reaction was carried out for 16 hours. The obtained reaction product was cooled to 80-90°C, 91.2 parts of tetrahydrophthalic anhydride were added, the reaction was carried out for 8 hours, and the product was taken out after cooling. The carboxyl group-containing vinyl ester resin thus obtained had a non-volatile content of 65% and an acid value of the solid content of 87.5 mgKOH / g.
[0078] The vinyl ester resin solution (varnish) of the above synthesis example was used, and the components and ratios (parts by weight) shown in Table 1 were blended and premixed with a stirrer, and then kneaded with a three-roll mill to prepare an alkaline developing resin composition. Furthermore, the thermal shock resistance (TCT test), high temperature storage stability (TS test), printability (covering ability, sagging), acid resistance, and stability (tin plating resistance, boil whitening resistance) were evaluated by the following methods.
[0079] [Table 1]
[0080] A: Carboxylic acid-containing vinyl ester resin of the synthesis example, solid content 65%, equivalent to the carboxyl group-containing vinyl ester resin of (5); F Pigment: Phthalocyanine Green, Pigment A manufactured by Dainippon Ink and Chemicals, Inc. F Defoamer: KS-66, manufactured by Shin-Etsu Chemical Co., Ltd. C Antioxidant: IRGANOX 1010, manufactured by BASF JAPAN LTD. B Photoinitiator: Omnirad 369 E, manufactured by IGM E Talc: LMP-100, manufactured by FUJI TALC INDUSTRIAL E Barium sulfate: B-30, manufactured by Sakai Chemical Industry Co., Ltd. H Solvent: PGMEA, propylene glycol monomethyl ether acetate G Epoxy resin: N-770-75EA, manufactured by DIC, novolac type multifunctional epoxy resin, solid content 75% D Compounds with two or more ethylenically unsaturated groups in one molecule: MT-3501G, manufactured by Zhangjiagang Dongya Di-Chi Biochemical Co., Ltd.
[0081] Performance evaluation (1) Thermal shock resistance (TCT test) The alkaline development type resin compositions of the Examples and Comparative Examples were applied to the entire surface of a substrate on which a 2 mm copper wire pattern had been formed by screen printing so as to have a thickness of 40 μm, and dried in a hot air circulation drying oven at 80° C. for 30 minutes. After cooling to room temperature, the coating was exposed to 400 mJ / cm 2 using an exposure device equipped with a high-pressure mercury lamp. 2 Then, the resist was developed with a 1 wt% aqueous sodium carbonate solution at a pressure of 0.2 MPa and a liquid temperature of 30°C for 60 seconds, and then cured in a hot air circulation drying oven at 150°C for 60 minutes. The cumulative exposure in the UV transfer oven was 2000 mJ / cm 2By irradiating ultraviolet rays under the above conditions, 17 evaluation boards having a right-angled resist pattern were fabricated for crack resistance during thermal cycles. The evaluation boards fabricated as described above were placed in a temperature cycler that performs thermal cycles at -40°C to 160°C, and a thermal shock cycle test (TCT test) was performed by setting different cycle numbers. Next, the appearance was observed for each number of cycles, and the number of cycles without cracks was recorded (see Figures 1 and 2 for the presence or absence of cracks), and the evaluation criteria are shown below. ◯: No cracks were observed even after 1000 cycles. ×: Cracks occurred within 1000 cycles.
[0082] (2) High-temperature storage stability (TS test) The evaluation boards were placed in an oven at 160° C. and set to stand for several different periods of time, and a cross-cut test was performed as follows: The maximum time during which no peeling occurred during the cross-cut test was recorded. Cross-cut test: After irradiating the board with ultraviolet light in the UV transfer furnace, a new cutter knife blade was used to apply a force at a 30° angle to the board surface, creating a grid pattern of cuts on the surface of the solder resist film, and a peel test was then performed using 3M tape (see Figure 3). ◯: The high-temperature storage time without peeling in the cross-cut test reached 1000 hours or more. ×: The high-temperature storage time during which peeling does not occur in the cross-cut test is less than 1000 hours.
[0083] (3) Covering ability The alkaline developing resin composition shown in Table 1 was printed by screen printing on the copper circuit of a printed wiring board, and then the coating state of the alkaline developing resin composition on a single circuit was observed, and the coating thickness of the alkaline developing resin composition on a copper corner was comparatively evaluated. The thickness of the copper circuit was about 70 μm (see FIG. 4). ◯: The coating thickness of the alkaline developing resin composition is 10 μm or more. ×: The coating thickness of the alkaline developing resin composition is less than 10 μm.
[0084] (4) Drooping A starting line was drawn on a large copper-clad substrate with an oil-based pen, and 0.2 ml of the alkaline developing resin composition was drawn up using a 1 ml disposable syringe, and the alkaline developing resin composition was applied to the copper-clad substrate. The large copper-clad substrate with the alkaline developing resin composition applied thereto was placed upright on a substrate holder and baked at 80°C for 30 minutes in a hot air circulation dryer. After drying, the length of the drip from the reference line was measured (see Figure 5). ○: The length of the drip is 5cm or less. ×: The length of the drip was longer than 5 cm.
[0085] (5) Acid resistance The alkaline development type resin compositions of the Examples and Comparative Examples were applied to the entire surface of a substrate on which a 2 mm copper wire pattern had been formed by screen printing so as to have a thickness of 40 μm, and dried in a hot air circulation drying oven at 80° C. for 30 minutes. After cooling to room temperature, the coating was exposed to 400 mJ / cm 2 using an exposure device equipped with a high-pressure mercury lamp. 2 Next, it was developed for 60 seconds in a 1 wt% sodium carbonate aqueous solution at a pressure of 0.2 MPa and a liquid temperature of 30°C, and then cured for 60 minutes at 150°C in a hot air circulation drying oven to produce an evaluation board with a solder resist film. This evaluation board was immersed in a 10 vol% H2SO4 aqueous solution at room temperature for 20 minutes, and penetration into the gap between the solder resist film and the board and dissolution of the solder resist film were visually confirmed, and peeling by tape peeling was also confirmed. ○: No change was observed. △: Slightly changed. ×: The coating film was blistered or swelled and fell off.
[0086] (6) Tin plating resistance (solder heat resistance) The alkaline development type resin compositions of the Examples and Comparative Examples were applied to the entire surface of a substrate on which a 2 mm copper wire pattern had been formed by screen printing so as to have a thickness of 40 μm, and dried in a hot air circulation drying oven at 80° C. for 30 minutes. After cooling to room temperature, the coating was exposed to 400 mJ / cm 2 using an exposure device equipped with a high-pressure mercury lamp. 2The pattern was exposed to light at 4000 K, and then developed with a 1 wt% aqueous solution of sodium carbonate at a pressure of 0.2 MPa and a liquid temperature of 30°C for 60 seconds, followed by curing for 60 minutes at 150°C in a hot air circulation drying oven to produce an evaluation board with a solder resist film. A rosin-based flux was applied to the solder resist film of this evaluation board. The evaluation board with the rosin-based flux applied was immersed in a solder bath previously set at 260°C, and the flux was washed off with denatured alcohol, after which the solder resist film was visually evaluated for swelling and peeling. The evaluation criteria are as follows: ◯: No peeling was observed even after immersion for 10 seconds was repeated three or more times. △: When immersed for 10 seconds three or more times, some peeling occurs. ×: When immersion for 10 seconds was repeated within 3 times, the solder resist film swelled and peeled off.
[0087] (7) Resistance to boil bleaching The alkaline development type resin compositions of the Examples and Comparative Examples were applied to the entire surface of a substrate on which a 2 mm copper wire pattern had been formed by screen printing so as to have a thickness of 40 μm, and dried in a hot air circulation drying oven at 80° C. for 30 minutes. After cooling to room temperature, the coating was exposed to 400 mJ / cm 2 using an exposure device equipped with a high-pressure mercury lamp. 2 Next, the substrate was developed with a 1 wt% aqueous sodium carbonate solution at a pressure of 0.2 MPa and a liquid temperature of 30°C for 60 seconds, and then cured in a hot air circulation drying oven at 150°C for 60 minutes to produce an evaluation board with a solder resist film. A rosin-based flux was applied to the solder resist film of this evaluation board. The evaluation board with the rosin-based flux applied was immersed in a solder bath previously set to 288°C for 10 seconds, and then immersed in boiling water for 30 minutes to observe whether the surface color turned white. ○: Not white. △: Slightly white. ×: Severely whitened.
[0088] As can be seen from the above, by adjusting the composition to Examples 1 to 4, the alkaline development type resin composition has good printability (covering property, sagging) and stability (tin plating resistance, boil whitening resistance), and an alkaline development type resin composition capable of obtaining a solder resist film excellent in all of thermal shock resistance, high temperature storage stability, and acid resistance can be obtained. In contrast, Comparative Example 1 does not use talc as a filler, and only barium sulfate is used, and Comparative Examples 2 and 3 have a low talc blending ratio in the filler, and no antioxidant is added in either case, resulting in poor thermal shock resistance, high temperature storage stability, and stability, as well as poor printability. In Comparative Example 4, the blending ratio of talc was increased to 40 parts by weight, and as a result, the stability (tin plating resistance, boil whitening resistance) tends to improve, but the thermal shock resistance, high temperature storage stability, and acid resistance are all poor, and the printability is also poor. In Comparative Example 5, an antioxidant was added in addition to Comparative Example 4, and as a result, acid resistance and stability (tin plating resistance, boil whitening resistance) were improved, but the thermal shock resistance and high temperature storage stability were poor, and printability was still poor. In Comparative Example 6, the total amount of filler used was increased in addition to Comparative Example 5, and as a result, high temperature storage stability, acid resistance, and stability (tin plating resistance, boil whitening resistance) were improved, and some printability (sagging) was also improved, but thermal shock resistance and covering properties were still poor. In contrast to Comparative Example 5, the Reference Example used only talc as a filler, and as a result, printability (covering properties, sagging) was excellent, and thermal shock resistance, high temperature storage stability, and ink stability (tin plating resistance, boil whitening resistance) were all improved, but acid resistance was poor.
Claims
1. (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) an antioxidant, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, The (E) inorganic filler contains talc, The content of the talc is 50% by weight or more when the total amount of the (E) inorganic filler is taken as 100% by weight, The alkaline developing resin composition according to claim 1, wherein the total content of the inorganic filler (E) is 60 to 180 parts by weight based on 100 parts by weight (solid content basis) of the vinyl ester resin (A).
2. 2. The alkaline developing resin composition according to claim 1, further comprising (F) another additive other than the (B) photopolymerization initiator and the (C) antioxidant.
3. 2. The alkaline developing resin composition according to claim 1, further comprising (G) an epoxy resin.
4. 2. The alkaline developing resin composition according to claim 1, further comprising (H) an organic solvent.
5. The alkaline developing type resin composition according to any one of claims 1 to 4, wherein an amount of the antioxidant (C) is 3 parts by weight or more relative to 100 parts by weight (converted into solid content) of the vinyl ester resin (A).
6. 5. The alkaline developing resin composition according to claim 1, wherein the inorganic filler (E) further contains barium sulfate.
7. 7. A photocurable dry film obtained by applying the alkaline developing resin composition according to claim 1 to a carrier film and drying the applied resin composition.
8. A coating film obtained by applying the alkaline developable resin composition according to any one of claims 1 to 6 to copper and drying it, or a cured product obtained by applying the alkaline developable resin composition to a carrier film, drying it, laminating the resulting photocurable dry film on copper, and photocuring the resulting coating film.
9. A printed wiring board comprising: a coating film obtained by applying the alkaline developable resin composition according to any one of claims 1 to 6 to a substrate having a copper circuit and drying the composition; or a cured product obtained by applying the alkaline developable resin composition to a carrier film, drying the composition, laminating the resulting photocurable dry film on a substrate having a copper circuit, photocuring the coating film, and then thermally curing the resulting cured product.
Citation Information
Patent Citations
Photocurable resin composition, dry film and cured product of the same, and printed wiring board using the same
JP2011164304A